The Role of Case Syncretism in Agreement Attraction: A Comprehension Study - Slioussar, Natalia; Magomedova, Varvara; Makarova, Polina (Frontiers in Psychology, 2022)
Many production and comprehension experiments have studied attraction errors in agreement, primarily in number (e.g. ‘The key to the cabinets were rusty’). Studies on gender agreement attraction are still sparse, especially in comprehension. We present two self-paced reading experiments on Russian focusing on the role of syncretism in this phenomenon. Russian nouns are inflected for case and number, and some forms have the same inflections (are syncretic). In several experiments on Slovak, Badecker and Kuminiak (2007) showed that both head and attractor syncretism play a role for gender agreement in production. We demonstrate for the first time that this is also the case in comprehension. The role of head noun syncretism has not been analyzed in any previous comprehension studies, also for number agreement. We conclude that syncretic forms create uncertainty, which is crucial for agreement disruption. These results are better compatible with retrieval approaches to agreement attraction. We discuss the implications of our findings for the nature of the retrieval cues used to establish morphosyntactic dependencies. The question whether case marking modulates agreement attraction in comprehension has also been addressed by Avetisyan, Lago, and Vasishth (2020) in a study on Armenian, and they found no evidence of such influence. We offer an explanation of the conflicting findings from several studies based on the syntactic constructions they used as materials.